"Yours is better!" Participant Response Bias in HCI - Dell, Nicola; Vaidyanathan, Vidya; Thies, Indrani Medhi; Cutrell, Ed; Thies, Bill (CHI 2012: Proceedings of the Conference on Human Factors in Computing Systems, 2012)
Although HCI researchers and practitioners frequently work with groups of people that differ signiﬁcantly from themselves, little attention has been paid to the effects these differences have on the evaluation of HCI systems. Via 450 interviews in Bangalore, India, we measure participant response bias due to interviewer demand characteristics and the role of social and demographic factors in inﬂuencing that bias. We ﬁnd that respondents are about 2.5x more likely to prefer a technological artifact they believe to be developed by the interviewer, even when the alternative is identical. When the interviewer is a foreign researcher requiring a translator, the bias towards the interviewer’s artifact increases to 5x. In fact, the interviewer’s artifact is preferred even when it is degraded to be obviously inferior to the alternative. We conclude that participant response bias should receive more attention within the CHI community, especially when designing for underprivileged populations.